An Advanced PLL-less Control Scheme for LVRT Capability with Harmonics Current Mitigations in Grid-Tied PV System Under Weak and Distorted Grid - Mishra M.K.; Mishra A.; Lal V.N. (My University, 2025)
This paper proposes an advanced phase-locked loop (PLL) less control scheme to mitigate the grid current harmonics along with enhanced low voltage ride-through (LVRT) capability of a grid-tied photovoltaic system (GTPVS) under the weak grid and distorted grid voltages. The enhanced LVRT operation of the GTPVS is achieved with the coordinated operation of the active power regulator (APR) and dynamic reactive power support (DRPS) controller. Moreover, an advanced phase compensated multiresonant (APCMR) current controller is utilized to mitigate the grid current harmonics under distorted grid voltages. The proposed control scheme is implemented in the αβ reference frame without park's transformation as well as a PLL unit. Thus, the computational burden of the proposed control scheme reduces. Further, the frequency adaptability of the GTPVS is improved during variations in grid frequency. To verify and evaluate the effectiveness of the proposed LVRTPLL-less control scheme (LPLCS) over the conventional LVRT PLL based control scheme (LPBCS), the experimental analysis is carried out using OPAL-RT OP 4510 real-time digital simulator. © 2022 IEEE.